Balancing Innovation and Burden: Evaluating the Impact of Curriculum Reform - Saparuddin, Muhammad; Heriman; Wartini, Sri; Warman; Bahzar, Mohammad; Nurlaili (Al-Qalam Institue, 2025)
Education is undergoing continuous transformation in response to rapid advancements in science, technology, and the dynamic demands of globalization. Within the context of the digital era and the Fourth Industrial Revolution, educational systems are expected to become increasingly adaptive and innovative. One of the central strategies in this transformation is the adoption of an innovation-based curriculum, which emphasizes interactive, flexible, and technology-driven approaches to learning. However, the implementation of such curricula is not without challenges. Key issues include unequal access to technology, the rising academic workload experienced by students, and the insufficient preparedness of teachers in adopting new pedagogical methods. Schools in rural or underdeveloped regions, for example, often face significant barriers due to limited infrastructure, while students are required to adapt to more independent and demanding learning processes. Moreover, teachers frequently lack adequate training, which hampers the effective application of innovative teaching strategies. To ensure sustainable benefits, the innovation-based curriculum must be introduced with careful planning, comprehensive teacher development, and equitable access to resources. Without such considerations, innovation risks becoming a burden for both students and educators rather than a genuine driver of educational improvement.